The Effect of Crossword Puzzle Application on The Students’ Learning Motivation in Science Learning - Tati Nurhayati; Dwi Anita Alfiani; Dewi Setiani (UIN Siber Syekh Nurjati Cirebon, 2019)
AbstractCrossword puzzle strategy is one strategy of active learning that involves all students to actively think by filling out crossword puzzles prepared by the teacher. So those students are expected to be more enthusiastic in participating in learning. This study aims to examine the effect of applying the crossword puzzle strategy on students' learning motivation in science learning. The research method used is a quantitative method, with the design of one shoot case study. The population in this study were all students of class amounting to 21 students, and using saturated sampling in determining the sample. Data collection techniques used are structured observation, questionnaires, and documentation. Furthermore, the results of the research data were tested using regression tests. The results showed that the significance value of the regression test was 0,000. Because significant value is smaller than 0.05 and t count (4.316) is greater than t table (1.72913), it can be concluded that Ha is accepted and Ho is rejected. This means that the implementation of crossword puzzle strategy has a significant effect on students' learning motivation in science learning.Keywords: crossword puzzle, students’ learning motivation, science learning. AbstrakStrategi crossword puzzle adalah salah satu strategi pembelajaran aktif yang melibatkan semua peserta didik untuk aktif berfikir dengan mengisi teka teki silang yang telah disiapkan oleh guru. Sehingga diharapkan peserta didik menjadi lebih antusias dalam mengikuti pembelajaran. Penelitian ini bertujuan untuk meneliti tentang pengaruh penerapan strategi crossword puzzle terhadap motivasi belajar siswa pada mata pelajaran IPA. Metode penelitian yang digunakan adalah metode kuantitatif, dengan desain one-shoot case study. Populasi dalam penelitian ini adalah semua siswa kelas V yang berjumlah 21 siswa, dan menggunakan sampling jenuh dalam menentukan sampelnya. Teknik pengumpulan data yang digunakan adalah observasi, angket dan dokumentasi. Selanjutnya data hasil penelitian diuji menggunakan uji regresi. Hasil penelitian menunjukkan bahwa nilai signifikansi pada uji regresi sebesar 0,000. Karena nilai signifikansi lebih kecil dari 0,05 dan t hitung (4.316) lebih besar dari t tabel (1.72913), maka dapat disimpulkan bahwa Ha diterima dan Ho ditolak. Hal ini berarti bahwa penerapan strategi crossword puzzle berpengaruh signifikan terhadap motivasi belajar siswa pada mata pelajaran IPA.Kata kunci : crossword puzzle, motivasi belajar siswa, pembelajaran IPA.